The effect of the awareness of taxpayer and tax socialization on taxpayer compliance for motor vehicles - Ramdhan, Rizky Mochammad; Rachman, Andry Arifian (International Journal of Financial, Accounting, and Management, 2023)
Purpose: This study aimed to determine whether taxpayer awareness and tax socialization affect taxpayer compliance at the SAMSAT Office of Cianjur Regency. Research methodology: This study used a simple random sampling technique and the Slovin method using Statistical Program for Society Science (SPSS) software. Primary data were obtained by distributing the questionnaires. Results: Based on the results, it can be concluded that the variable awareness of taxpayers and tax socialization partially have a positive and significant effect on taxpayer compliance. Limitations: This study's limitation is the use of a questionnaire to obtain data, which allows the respondent to translate the questionnaire items differently from what the author intended. The questionnaire was distributed only to the taxpayer of a motor vehicle at the SAMSAT Office of Cianjur Regency. Contribution: Author, SAMSAT Office, and Public.